Genomic insights into multidrug - resistant Salmonella enterica isolates from pet dogs and cats - Jiratchaya Puangseree; Si Thu Hein; Rangsiya Prathan; Songsak Srisanga; Rungtip Chuanchuen (Scientific Reports)
Abstract Companion animals are recognized as potential reservoirs and transmitters of antimicrobial resistance (AMR) within the One Health framework. However, in-depth knowledge on AMR in pet animals remains limited. This study aimed to characterize Salmonella from companion dogs and cats using Whole Genome Sequencing (WGS). A total of 25 Salmonella obtained from clinically healthy household dogs and cats were serotyped and had their antimicrobial susceptibility tested. A discrepancy between the serovars identified by traditional slide agglutination tests and those determined by WGS analysis was observed. The isolates exhibited multidrug resistance (MDR) (n = 18) and harbored several resistance genes either chromosomally encoded or plasmid associated. Tn3 and IS26 were commonly found flanking AMR genes and class 1 integrons, while an unusual qacL-IS256-sul3 arrangement was also frequently observed. Similar AMR genes and insertion sequences were found among dogs and cats from different provinces, suggesting clonal spread and horizontal gene transfer of AMR. The similarity between plasmids (i.e., IncX1 and IncI1 plasmid) carrying AMR genes (e.g., aadA1, qacL, sul3, bla TEM-1B, qnrS1, dfrA, tetA) in Salmonella from pets in this study and those from other sources (e.g., humans, food producing animals and environment) in different countries was revealed, suggesting that pet dogs and cats may play a significant role in the global spread of AMR. The finding underscores the role of household pets as silent reservoirs of MDR Salmonella and the need for a One Health approach to tackle the issue. Public health campaigns promoting hygiene practices among pet owners should be encouraged. Pet animals should be incorporated into AMR monitoring and surveillance programs as a component of One Health framework.